The Research on Improved Companding Transformation for Reducing PAPR in Underwater Acoustic OFDM Communication System - Jinqiu Wu; Gang Qiao; Xiaofei Qi (Discrete Dynamics in Nature and Society)
To solve the problem of the high peak-to-average power ratio (PAPR) in Orthogonal Frequency Division Multiplexing (OFDM) for the underwater acoustic communication system, the paper offers a method of reducing PAPR which combines the amplitude limiting and the improved nonlinear transformation. Traditional amplitude limiting technique can reduce PAPR in OFDM system effectively, at the cost of reducing the bit error rate (BER). However the companding transformation has far less computation complexity than SLM or PTS technologies and can improve the BER performance compared to the amplitude limiting technique simultaneously. The paper combines these two kinds of techniques, takes full use of advantages of the two method, and puts forward a low-complexity scheme choosing parameters that are more appropriate to the underwater acoustic field, with the result of improved BER performance even in lower SNR. Both simulation and experiment results show that the new method which combines clipping and companding transformation can effectively reduce the PAPR in the underwater acoustic OFDM communication system and improve the BER performance simultaneously.